A Double-Blind Placebo-Controlled Trial of levetiracetam for Global Severity in Child Autism Spectrum Disorders - Aliyev, N. A.; Aliyev, Z. N. (International Journal of Innovative Research in Medical Science, 2018)
Objectives: The effects of levetiracetam and placebo on global severity were compared in Child Autism Spectrum Disorders (ASD). Materials and methods: Childs with ASDs were enrolled in a 12-week double-blind placebo-controlled levetiracetamtrial. Fifty were randomly assigned to levetiracetam (n=50) or placebo (n=50).The mean maximum dosage for levetiracetamwas 950.50±279.19 mg/day Repetitive behaviors were measured with the Clinical Global Impression (CGI) improvement scale. Results: There was a significant treatment-by-time interaction indicating a significantly greater reduction in repetitive behaviors across time for levetiracetamthan for placebo. With overall response defined as a CGI global improvement score of 2 or less, there were significantly more responders at week 12 in the levetiracetamgroup than in the placebo group. The risk ratio was 1.5 for CGI global improvement (responders: levetiracetam, 50%; placebo, 10%). Side effects were not observed. Conclusions: levetiracetamtreatment, compared to placebo, resulted in significantly greater improvement in global severity behaviors, according to CGI rating scale. levetiracetamappeared to be well tolerated movement score of 2 or less, there were significantly more responders at week 12 in the levetiracetamgroup than in the placebo group. Side effects were not observed.